Paradella tiffany sp. nov., a distinctive sphaeromatid isopod (Crustacea: Isopoda: Sphaeromatidea) from Baja California, Mexico - Bruce, Niel L.; Wetzer, Regina (Zootaxa, 2004)
Paradella tiffany sp. nov., from the high intertidal of Baja California, Mexico, is described and figured. It is the first record of a species of Paradella with a posteriorly-directed median process on pereonite 7, this character distinguishing males of the species from all other species in the genus and all other sphaeromatids known from the East Pacific. A further unique character, in the male only, is the presence of short, stout and rigid plumose marginal setae on the distal margin of the pleopod 1 endopod.